2019
DOI: 10.1080/17429145.2019.1618503
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular responses of flax to 24-epibrassinosteroide seed priming under drought stress

Abstract: The effects of 24-epibrassinolide (24-epiBL 10 −8 M) were investigated on antioxidant enzymes activity, lipid peroxidation, and genes expression in 10-day-old Linum usitatissimum L. seedlings subjected to 6%, 12%, and 18% polyethylene glycol (PEG). Water deficit significantly enhanced the activity of CAT, POD, and SOD enzymes as well as elevation in protein, proline, and MDA contents whereas decreased activity of APOX and NR in a concentration-dependent manner. 24-epiBL seed priming improved flax adaptability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The highest amount of MDA was produced in the first year of the experiment ( Figure 3 A). In this research, like other investigations done on bananas [ 32 ], wheat [ 19 ] and chickpea [ 33 ], the lipid peroxidation significantly increased by increasing the severity of water limitation ( Figure 4 A), which indicated that more oxidative damage occurred [ 19 ]. According to these assertations, the obtained results and the data represented in Table 4 , the severity of drought stress was greater in year one than in year two.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The highest amount of MDA was produced in the first year of the experiment ( Figure 3 A). In this research, like other investigations done on bananas [ 32 ], wheat [ 19 ] and chickpea [ 33 ], the lipid peroxidation significantly increased by increasing the severity of water limitation ( Figure 4 A), which indicated that more oxidative damage occurred [ 19 ]. According to these assertations, the obtained results and the data represented in Table 4 , the severity of drought stress was greater in year one than in year two.…”
Section: Discussionsupporting
confidence: 81%
“…APX is recognized as the most important peroxidase in H 2 O 2 detoxification [ 19 ]. The application of brassinolide at 1 μM concentration had the greatest impact on APX activity ( Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline and free amino acids content were accumulated in quinoa seeds treated with all treatment (Table 5). In agreement with our findings, there is a report revealing an increase in the proline content following application of brassinosteroids (28-HBL and 24-EBL) in sorghum and flax plants 46,47 .…”
Section: Discussionsupporting
confidence: 93%
“…Aside from higher antioxidant enzyme activities, their transcript levels ( FeSOD , POD , and CAT ) increased by EBR application under drought stress and play a role in conferring drought tolerance. The higher expression of MnSOD , POD1 , and POD3 in flax [ 71 ], Cu/Zn-SOD in common beans [ 72 ], Cu/ZnSOD and CAT in rice [ 73 ] under drought stress due to EBR application can also curb oxidative stress at gene transcript levels. The results of this study showed that EBR application under drought stress increased the activities of SOD, POD, and CAT and upregulated FeSOD , POD , and CAT genes, along with a higher accumulation of proline ( P5CS1 gene transcript levels) and SS ( Figure 9 ), all of which decrease ROS levels and help tobacco plants to adapt to drought stress.…”
Section: Discussionmentioning
confidence: 99%